SIRT7 and p53 interaction in embryonic development and tumorigenesis - Vazquez, Berta N.; Fernández-Duran, Irene; Hernandez, Yurdiana; Tarighi, Shahriar; Thackray, Joshua K.; Espinosa-Alcantud, Maria; Kumari, Poonam; Ianni, Alessandro; Cesaire, Lionel; Braun, Thomas; Esteller, Manel; Tischfield, Jay; et al. (Frontiers in Cell and Developmental Biology, 2024)
p53 is a hallmark tumor suppressor due in part to its role in cell cycle progression, DNA damage repair, and cellular apoptosis; its protein activity interrelates with the Sirtuin family of proteins, major regulators of the cellular response to metabolic, oxidative, and genotoxic stress. In the recent years, mammalian Sirtuin 7 (SIRT7) has emerged as a pivotal regulator of p53, fine-tuning its activity in a context dependent manner. SIRT7 is frequently overexpressed in human cancer, yet its precise role in tumorigenesis and whether it involves p53 regulation is insufficiently understood. Depletion of SIRT7 in mice results in impaired embryo development and premature aging. While p53 activity has been suggested to contribute to tissue specific dysfunction in adult Sirt7 -/-mice, whether this also applies during development is currently unknown. By generating SIRT7 and p53 double-knockout mice, here we show that the demise of SIRT7-deficient embryos is not the result of p53 activity. Notably, although SIRT7 is commonly considered an oncogene, SIRT7 haploinsufficiency increases tumorigenesis in p53 knockout mice.Remarkably, in specific human tumors harboring p53 mutation, we identified that SIRT7 low expression correlates with poor patient prognosis. Transcriptomic analysis unveils a previously unrecognized interplay between SIRT7 and p53 in epithelial-to-mesenchymal transition (EMT) and extracellular matrix regulation with major implications for our understanding of embryonic development and tumor progression.